Gregory's Pediatric Anesthesia. - Gregory, George A., 1934-; Andropoulos, Dean B. (Chicester : John Wiley & Sons, 2011)
Millions of pediatric patients receive anesthetics every year, but it has been established that those under 12 months of age have a higher risk of poor outcomes. Well established at the forefront of the field, and founded and edited by one of its modern pioneers, Pediatric Anesthesia is renowned for the excellence of its practical guidance. Aimed at pediatric anesthetists, anesthetists, and trainee anesthetists, this new edition covers the use of anesthesia on newborns to young adults, placing a strong emphasis on the most recent and important information from research and publications.
CHAPTER 39: Pediatric Anesthesia in Developing Countries; Part 4: Quality, Outcomes, and Complications in Pediatric Anesthesia; CHAPTER 40:Clinical Complications in Pediatric Anesthesia; CHAPTER 41: Impact of Pediatric Surgery and Anesthesia on Brain Development; CHAPTER 42: Patient Simulation and Its Use in Pediatric Anesthesia; CHAPTER 43: Databases and Outcome Research in Pediatric Anesthesia; CHAPTER 44: Electronic Anesthesia and Medical Records; CHAPTER 45: Operating Room Safety, Communication, and Teamwork.
APPENDIX A: Pediatric Anesthesia Drugs and Other Treatments in the Perioperative Period.
Print version record.
Keywords: Pediatric anesthesia; Anesthesia; Child; Infant; Medicine; Pediatric anesthesia; Electronic books